2022
DOI: 10.1186/s12978-022-01376-z
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive, cross-sectional study of postpartum education: midwives’ self-reported knowledge and teaching of postpartum complications in Ghana

Abstract: Background Obstetric complications remain the leading causes of maternal deaths. Since it is not always possible to ascertain which women will develop complications and which women will not, all women who have a baby should be educated about warning signs of complications. In this study, we assessed postpartum education provided by midwives, midwives’ knowledge to teach patients about complications and their skills to manage postpartum complications. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In patients after neuraxial block with lumbar pain, fecal/ urinary incontinence, or motor/sensitivity deficits that do not improve with time, it is mandatory to perform preferably an MRI to rule out compressive lesions such as epidural hematoma. 4,14,15 | 833 MOITA GONÇALVES et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients after neuraxial block with lumbar pain, fecal/ urinary incontinence, or motor/sensitivity deficits that do not improve with time, it is mandatory to perform preferably an MRI to rule out compressive lesions such as epidural hematoma. 4,14,15 | 833 MOITA GONÇALVES et al…”
Section: Discussionmentioning
confidence: 99%
“…Associated risk factors of obstetric neurologic injuries are primiparity, instrumental delivery, and regional anesthesia. In patients after neuraxial block with lumbar pain, fecal/urinary incontinence, or motor/sensitivity deficits that do not improve with time, it is mandatory to perform preferably an MRI to rule out compressive lesions such as epidural hematoma 4,14,15 …”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported that postpartum women in transitional countries experience inadequate knowledge of postpartum warning signs of complications [11][12][13][14]. Furthermore, midwives working in Tamale, Ghana, have self-reported inadequate knowledge and skill sets to adequately educate patients about all detrimental postpartum complications and how to manage those complications [15,16].…”
Section: Introductionmentioning
confidence: 99%